MiR-27a-3p/Hoxa10 Axis Regulates Angiotensin II-Induced Cardiomyocyte Hypertrophy by Targeting Kv4.3 Expression - Cao, Xuefeng; Zhang, Zheng; Wang, Yu; Shan, Weichao; Wang, Ruiting; Mao, Shufang; Ding, Shi; Pang, Chong; Li, Baoqun; Zhou, Jian; Guo, Xiaoyan; Guo, Na; et al. (Frontiers in Pharmacology, 2021)
Cardiac hypertrophy is a common pathological process of various cardiovascular diseases, which is often accompanied with structural and electrical remodeling and can even lead to sudden cardiac death. However, its molecular mechanism is still remain largely unknown. Here, we induced cardiomyocyte hypertrophy by angiotensin II (Ang II), and found that miR-27a-3p and hypertrophy-related genes were up-regulated. Further studies showed that miR-27a-3p-inhibitor can alleviate myocardial hypertrophy and electrical remodeling. Moreover, luciferase assay confirmed that miR-27a-3p could regulate the expression of downstream Hoxa10 at the transcriptional level by targeting at its 3’UTR. At the same time, the protein expression of Hoxa10 was significantly reduced in Ang II-treated cardiomyocytes. Furthermore, overexpression of Hoxa10 can reverse myocardial hypertrophy and electrical remodeling induced by Ang II in cardiomyocytes. Finally, we found that Hoxa10 positively regulated the expression of potassium channel protein Kv4.3 which was also down-regulated in hypertrophic cardiomyocytes. Taken together, our results revealed miR27a-3p/Hoxa10/Kv4.3 axis as a new mechanism of Ang II-induced cardiomyocyte hypertrophy, which provided a new target for clinical prevention and treatment of cardiac hypertrophy and heart failure.